Trust and Acceptance of E-Banking Technology Effect of Mediation on Customer Relationship Management Performance - Ari Pambudi; Riya Widayanti; Primasatria Edastama (ADI Journal on Recent Innovation, 2021)
The application of E-Banking is a form of bank service to customers that was established in the 1970s and has started in Malaysia. There was a form of innovation that technology gave to electronics in 1981 into the world of the banking industry. The first was the introduction of Automated Teller Machines. On June 1, 2000, the Central Bank of Malaysia was officially established and gave permission to improve the form of service and convenience for customers when conducting online transactions which previously were done offline and could not be done anywhere. Banking in Indonesia has the advantage of instilling harmony in business ideals and values ??that lead to spirituality. A good relationship in building relationships is the standard for choosing a private bank. Where certain conditions banking is able to become mobile on online applications. It has been seen that there is less activity in bank lobbying in conducting transactions between customers and employees, because it has increased customer satisfaction, maintaining relationships with antecedent factors and marketing performance in the field. For this reason, CRM performance has a goal in building and maintaining good relationships, the nature of buyers and customer retention from the responses given. In a traditional commercial society, the physical form that can be seen is trust. The banking world is not far from the name of marketing and management as attracting forms of customer trust by providing products, services and buyer behavior by displaying employee performance. The application of strategies in marketing is a form of reference in attracting customers to become regular customers with the main purpose of this research paper being to analyze CRM performance as a form of trust in customer relationships to E-Banking without meeting bank employees, bringing convenience to customers in using banking e-banking services. accessible online.